REFINING UNIVERSITIES’ ROLE FOR WORLD PEACE: MOLDING ENLIGHTENED GRADUATES - Lai, Fong Woon (2004)
Today, in the midst of intense global political and religious strife, world peace can no longer be taken for granted. More disconcertingly, many who mastermind acts of violence or terrorism are highly educated individuals, holding university degrees. Because universities‟ influence is immensely far-reaching, there is an urgency for universities to re-look and refine their role in order to help regain world peace. Indeed, universities hold the power to mold future generations, whose outlook would either foster or annihilate world peace. As such, this paper proposes that universities look towards producing enlightened graduates. To do this, universities should firstly, revolutionize curriculum by increasing the requirement for general education to enhance students‟ understanding of world major cultures, faiths and beliefs. Secondly, universities should champion multiculturalism through active inter-cultural interaction driven by a diverse student population mix. Universities should promote and emphasize inter-cultural understanding and tolerance through academic and administrative officials. Thirdly, all university students should have exposure to an overseas stay while conducting research before they complete their undergraduate studies. Underlying this three-pronged approach is the objective of not merely enhancing the marketability of our graduates, but more importantly, preserving a peaceful environment within which they are able to contribute positively. Perhaps through such channels, world peace will once again reign foremost in the hearts and minds of man.